Perancangan Model dan Kuisoner Pengukuran Kinerja UMKM melalui Technology-Organization-Environment - Winda Wulandari; Meinarini Catur Utami; Elvi Fetrina (Fakultas Teknik Universitas Persada Indonesia YAI, 2022)
MSMEs (Micro, Small and Medium Enterprises) as one of the factors driving the economy inIndonesia are experiencing the Covid-19 pandemic crisis which has led to the activities of theIndonesian people. This will indirectly affect the activities of human life, including the buyingand selling process. Buying and selling activities that are usually carried out face-to-face can notbe carried out normally due to activities from the government so that it indirectly affects the salesresults of business actors, including MSME actors. During this pandemic, there was a verysignificant decline and caused deep anxiety for MSME actors such as payment of employeesalaries, daily operational costs, and others. The existence of this phenomenon or incident hasresulted in MSMEs having to rack their brains in order to survive in the midst of the ongoingcrisis. In order to continue to survive, MSMEs use social media to promote sales, or make salesonline with social media. The purpose of this study was to determine the effect of social mediaadoption on the performance of MSMEs. This research method is carried out in several stageswhich include problems, literature review about the research model, research design, makinginstruments that produce questionnaires. The result of this study is produces a research modelrelated to the adoption of social media on the performance of MSMEs which is supported by the dependent variable of the Technology-Organization-Environment (TOE) framework, as well as aquestionnaire.